Rituais de luto em tempos de pandemia de Covid-19: uma revisão narrativa - Barros, Raquel Ramos Barbosa (Brasil, 2023)
Human coexistence with death throughout its history includes wars, natural disasters, genocides and social inequalities and the lack of adequate medical care is one of the daily risk situations that has occurred since the arrival of COVID – 19. mourning rituals that we had to quickly get used to, as the lack of contact with the loved one was almost impossible. This research used the literature narrative review instrument to obtain results that theoretically support a clear and broad objective in order to exemplify facts within the pandemic we are experiencing. In this scenario, the psychologist assists these people in their grieving process and also helps to start the grieving process within therapy, whether individual or in a group. The listening process is very important to respect the patient's time, as listening generates acceptance and the absence of the wake brings with it the feeling of impotence and lack of acceptance of suffering in relation to the loss. This helplessness has been aggravated by social distancing, therefore, the psychologist's contact with the patient must provide the support previously denied and make the person accept the loss in a healthy way so that he can return to his domestic social environment.